2023
DOI: 10.3389/fphys.2023.1127689
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in musculoskeletal injury and disease risks across the lifespan: Are there unique subsets of females at higher risk than males for these conditions at distinct stages of the life cycle?

Abstract: Sex differences have been reported for diseases of the musculoskeletal system (MSK) as well as the risk for injuries to tissues of the MSK system. For females, some of these occur prior to the onset of puberty, following the onset of puberty, and following the onset of menopause. Therefore, they can occur across the lifespan. While some conditions are related to immune dysfunction, others are associated with specific tissues of the MSK more directly. Based on this life spectrum of sex differences in both risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 282 publications
0
17
0
Order By: Relevance
“…Notably, acute inflammatory responses differ between male and female rats, as well as in humans. Prior reports have shown that males are more susceptible to traumatic injury ( 94 , 95 ). However, the utilization of only male rats in this study is justified, considering that fewer than 3% of severely combat-injured service members in recent conflicts were female ( 96 ).…”
Section: Discussionmentioning
confidence: 98%
“…Notably, acute inflammatory responses differ between male and female rats, as well as in humans. Prior reports have shown that males are more susceptible to traumatic injury ( 94 , 95 ). However, the utilization of only male rats in this study is justified, considering that fewer than 3% of severely combat-injured service members in recent conflicts were female ( 96 ).…”
Section: Discussionmentioning
confidence: 98%
“…The short Form-36 Physical Functioning Scale (SF36 PFS) questionnaire is a set of patient self-reporting measures to indicate health status. The SF-36 PFS is composed of 10 items encompassing a hierarchical range of difficulties on everyday activities, including vigorous activities, moderate activities, lifting/carrying, climbing stairs, bending/kneeling/stooping, and walking, etc., and it has been used as a reliable and valid “stand-alone” instrument in research describing activity limitations in the elderly living in the community, and patients with different minor pathophysiological conditions and chronic diseases 39 41 . These results strongly suggest that G/A ratio could be a potential circulating biomarker to indicate change in physical performance, particularly mobility performance in males.…”
Section: Discussionmentioning
confidence: 99%
“…The sex difference pattern in COVID-19 related MSK disorders observed in this review is consistent with earlier submissions. Specifically, Hart [ 36 ] suggests that the higher risk for injuries to tissues of the MSK system in females is attributable to hormonal changes across lifespan, but markedly at onsets of puberty and menopause; gene expression independent of sex hormones; and immune dysfunction. In line with the foregoing, Wolf et al [ 37 ] conclude that structural anatomy differences, hormones, and genetics are important considerations in sex difference in MSK disorders between males and females.…”
Section: Discussionmentioning
confidence: 99%